Are medical graduates ready to face the challenges of Foundation training?. Issue 1031 (20th June 2011) - Tallentire, Victoria R; Smith, Samantha E; Wylde, Keith; Cameron, Helen S
Abstract : Purpose of study: Previous research demonstrates that graduating medical students often feel unprepared for practice and that their perceptions of preparedness correlate only partially with those of their supervising consultants. This study explores the components of preparedness for practice from the perspectives of both newly qualified doctors and their educational supervisors. Study design: A questionnaire study was undertaken at the University of Edinburgh, involving feedback on preparedness for practice over three consecutive years from 2007 to 2009, against 13 major programme outcomes, from graduates and their educational supervisors. In addition, free text responses were sought and thematically analysed. Results: Graduates consistently felt well prepared in consultation and communication skills but less prepared in acute care and prescribing. Educational supervisors consistently felt that graduates were well prepared in information technology and communication skills but less prepared in acute care and practical procedures. Free text analysis identified four main themes: knowledge; skills; personal attributes; and familiarity with the ward environment. Conclusions: Preparedness for practice data can be enriched by repeated collection over several years, comparison of different perspectives, and incorporation of free text responses. The non-technical skills of decision-making, initiative, prioritisation, and coping with stress are important components of preparing new doctors for practice. Education for Foundation trainees should focus on the areas in which graduates are perceived to be less prepared, such as acute care, prescribing, and procedural skills.